Attack In the Process of Competitive Activity in Taekwondo Analysis of Evaluation of Actions (Zien Journal of Social Sciences and Humanities, 2023)
In our research, we stopped at the suggestion of M.A. Godik (1966, 1982), who believes that control methods and objects used in martial arts competitions relate to the size, variety and effectiveness of offensive and defensive actions. Competition activities in three competitions of national importance were recorded and analyzed, they were later operationally processed with the use of computer technology.